Early stage health technology assessment (HTA) of biomedical devices: the MATCH experience - Pecchia, Leandro; Craven, Michael P. (Springer, 2013)
Early stage Health Technology Assessment (HTA) of biomedical devices requires different methods than those usually employed for pharmaceuticals. This paper reviews widely used methods for HTA, discusses their limits for early stage evaluation of biomedical devices and presents two methods for early stage HTA being developed in the Multidisciplinary Assessment of Technology Centre for Healthcare (MATCH) project: Analytic Hierarchy Process (AHP) to elicit user needs; and early stage economic evaluations using Markov Models.